Viability of Staphylococcus aureus and expression of its toxins (SEC and TSST-1) in cheeses using Lactobacillus rhamnosus D1 or Weissella paramesenteroides GIR16L4 or both as starter cultures - Silva, G.O.; Castro, R.D.; Oliveira, L.G.; Sant'Anna, F.M.; Barbosa, C.D.; Sandes, S.H.C.; Silva, R.S.; Resende, M.F.S.; Lana, A.M.Q.; Nunes, A.C.; Cerqueira, M.M.O.P.; Souza, M.R. (Journal of dairy science, 2020)
Staphylococcus aureus is one of the main causative agents of food poisoning. This bacterium is an important component of cheese microbiota and plays an important role in foodborne diseases. Another important component of the microbiota is the lactic acid bacterium, which actively participates in processes that define the physicochemical, sensorial, and microbiological features of cheese. Of the various microbiological interactions in cheese, the interaction between lactic acid bacteria and Staph. aureus is most relevant. To this end, we evaluated the viability of Staph. aureus strains and the expression of their enterotoxins in cheeses produced experimentally, using Weissella paramesenteroides GIR16L4 or Lactobacillus rhamnosus D1 or both as starter cultures. Over 7 d, we observed that the presence of lactic acid bacteria did not impair Staph. aureus growth. However, via qPCR we observed a change in the gene expression of staphylococcal enterotoxins, suggesting that molecular communication exists between Staph. aureus strains and lactic acid bacteria in cheese.